ANALISIS KOGNITIF KONSEPSI MAHASISWA TENTANG PERCEPATAN PADA AYUNAN SEDERHANA - Wiyanto, - (Universitas Negeri Semarang, 2008)
The purpose of this study was to explore the physics teacher studentÃ¢â¬â¢sconception and the reasoning of their conception regarding the acceleration of asimple pendulum. A paper-pencil test was conducted to explore their conception of theacceleration concept at this case. Thirty second-year-students were asked to specifywhether the acceleration of the pendulum is zero at the indicated points, and to specifyits direction if it is not zero. Based on the result of the test, an interview wasconducted to the students for analysing the underlying cognition (reasoning) of theiranswers. The result of this study showed that all of students could not draw thedirection of the acceleration. Additionally, there were three groups of students basedon the cognitive analysis. The first group was the most students (50%) that hadconfusion of the acceleration definition, so they were unable to interpret it properly.The second one was some students (30%) that assumed the pendulum oscillation is asa simple harmonic motion, in which the acceleration at its equilibrium point is zero.The last group was the others (20%) that considered the pendulum oscillation is as apart of an uniform circular motion, in which the acceleration is always toward thecentre.Kata kunci: analisis kognitif, percepatan, ayunan sederhana